Sedation in the intensive care unit (ICU) and procedural sedation: clinical guidelines and personal practice - O Budniuk; I Yovenko; D Havrychenko (Медицина болю, 2025)
The presented literature review describes key issues of sedation in ICU patients and procedural sedation during medical examinations and manipulations. Attention is paid to issues of monitoring the depth of sedation and vital functions to ensure patient safety. Modern clinical guidelines are analyzed, emphasizing an individualized approach for each patient, selecting the minimal sedation that allows the patient to be easily awakened, feel comfortable, and have adequate pain control unless the clinical situation requires deeper sedation. The focus is placed on the contemporary concept of sedation: a "calm, comfortable, and cooperative" patient. The characteristics of pharmacological agents widely used for sedation — dexmedetomidine, midazolam, and propofol — are reviewed. Their advantages and disadvantages are described, along with a comparative analysis. Information on the authors' own experience with various sedation protocols in ICU and procedural sedation is also presented.